2018
DOI: 10.1038/s41477-018-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

A group of receptor kinases are essential for CLAVATA signalling to maintain stem cell homeostasis

Abstract: Continuous organ initiation and outgrowth in plants relies on the proliferation and differentiation of stem cells maintained by the CLAVATA (CLV)-WUSCHEL (WUS) negative-feedback loop. Leucine-rich repeat receptor-like protein kinases (LRR-RLKs), including CLV1, BARELY ANY MERISTEMS and RECEPTOR-LIKE PROTEIN KINASE 2 (RPK2), a receptor-like protein CLV2 and a pseudokinase CORYNE (CRN) are involved in the perception of the CLV3 signal to repress WUS expression. WUS, a homeodomain transcription factor, in turn di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
154
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 31 publications
2
154
0
Order By: Relevance
“…Peptide hormones in plants are almost exclusively perceived by LRR family receptor kinases and receptor‐like proteins through the formation of homomers or heteromers (Hirakawa et al 2017). Genetic and biochemical assays showed that CLERK functions redundantly with three closely related LRR receptor kinases, CIK1, CIK3 and CIK4, to maintain stem cell homeostasis in the SAM (Hu et al 2018). CLV2 that interacts with CRN regulates stem cell homeostasis in the SAM through sensing the CLV3 peptide (Bleckmann et al 2010; Zhu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Peptide hormones in plants are almost exclusively perceived by LRR family receptor kinases and receptor‐like proteins through the formation of homomers or heteromers (Hirakawa et al 2017). Genetic and biochemical assays showed that CLERK functions redundantly with three closely related LRR receptor kinases, CIK1, CIK3 and CIK4, to maintain stem cell homeostasis in the SAM (Hu et al 2018). CLV2 that interacts with CRN regulates stem cell homeostasis in the SAM through sensing the CLV3 peptide (Bleckmann et al 2010; Zhu et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…SERKs as essential co-receptor kinases (Hu et al, 2018;Cui et al, 2018;Anne et al, 2018;Smakowska-Luzan et al, 2018;Zhang et al, 2017).…”
Section: Recent Genetic Biochemical and Structural Evidence Suggest mentioning
confidence: 99%
“…) and CIK co‐receptors (Hu et al . ), the second through the receptor‐like protein CLAVATA2 (CLV2; Kayes & Clark ) that acts in complex with the pseudokinase CORYNE (CRN; Müller et al . ).…”
Section: Post‐translationally Modified Peptides and Peptide Familiesmentioning
confidence: 99%